MULTIPLICATIVE EVALUATION OF INFLUENCE OF THE ORGANIZATIONAL RISK FACTORS ON FLIGHT SAFETY IN AIR TRAFFIC CONTROL - Sikirda, Yuliya; Tetiana Shmelova, Tetiana Shmelova; Tkachenko, Dmytro (Proceedings of National Aviation University, 2018)
Purpose: to systematize the risk factors of organizational nature in Air Traffic Control system and to evaluate their complex influence on flight safety. Methods: the hazard degree of organizational factors in air traffic control has determined by the method of expert assessments, the scale of acceptability (admissibility) of the risk factors of organizational nature has constructed on the basis of the fuzzy sets theory with the use of linguistic variables. Results: it has revealed that air traffic control systems and equipment have the most significant influence on flight safety, company management and structure – the least one. The multiplicative function for evaluation of the flight safety in air traffic control has obtained, which allows checking the conformity of the values of organizational risk factors to the maximum permissible level of hazard. Discussion: proposed methodology for evaluation of the organizational risk factors influence on flight safety in air traffic control will allow developing the safety passports that can be applied by the State Aviation Administration of Ukraine during the certification inspections of air navigation service providers to compare the normative and actual indicators of their activities.